IMPLEMENTATION OF THE VILLAGE FINANCIAL SYSTEM IN BANGIO VILLAGE, PINOGU SUB-DISTRICT BONE BOLANGO DISTRICT - yulandri tobuto; Titin Dunggio; Nuzmerini Rauf (Journal of Economic, Business, and Administration (JEBA), 2022)
The purpose of this study was to determine the application of the SISKEUDES application and the inhibiting factors in the application of the SISKUDES application in village financial management in Bangio Village, Pinogu District, Bone Bolango Regency. The research methodology in writing this final report is a descriptive qualitative method with the type of field research. The data collection techniques used are observation, interviews and documentation which are primary data, which comes from eight informants who provide information directly related to the implementation of the SISKEUDES application. From this research, it can be concluded that the SISKEUDES application in Bangio village financial management plays an important role in assisting village officials because it facilitates and is useful in preparing village financial reports accurately. The SISKEUDES application is also useful and effective in generating financial reports for villages for security and helping improve the performance of village officials.